Pengukuran Implicit Association terhadap Istilah yang Berkaitan dengan Narkoba pada Remaja SMA - Salwa Azzahra; Andhita Nurul Khasanah (UNISBA Press, 2023)
The problem of drugs in Indonesia is becoming serious because the cases are increasing among teenagers. The National Narcotics Agency has carried out various prevention program efforts, one of which is the